Prise en charge pluridisciplinaire des risques psychosociaux : un premier état des lieux auprès des médecins du travail, des inspecteurs du travail et des psychologues du travail - Elsa Laneyrie; Aurélie Landry (Perspectives Interdisciplinaires sur le Travail et la Santé)
Psychosocial risk preventers often complain of excessive workload and professional isolation. Multidisciplinary work, which is encouraged by France’s current legislative and regulatory framework, could be a solution. The objective of this action-research is to understand how, in a context of increasing psychosocial risks, we can foster collaborative practices between labour inspectors, occupational health doctors, and occupational psychologists. We examined the responses of a sample of 32 subjects who answered questions about a typical case of a psychosocial risk they would be likely to encounter in their work. Qualitative analysis showed that preventers ignored the functions and duties of the other two groups. Nonetheless, all the professionals stated that multidisciplinary work was important. These results point to initial recommendations for the fostering of multidisciplinary prevention. Indeed, this type of support is often noted in the literature and laws as being the most effective in reducing occupational risks.